Example of Positioning Intermodal Terminals on Inland Waterways - Brnjac, Nikolina; Ćavar, Ivana (Promet - Traffic&Transportation, 2012)
Positioning of intermodal terminals is of key importance since it affects the very investment into the terminal, ecological, physical issues and the costs of the operation of individual terminals. Detailed analysis has to be performed by decision-making regarding the siting of intermodal terminals. The work analyzes the relevant criteria necessary for the siting of intermodal terminals. The problem of the proposed research is the structure of intermodal systems in the Republic of Croatia with the case study of inland waterways. The research and the study of the characteristics of intermodal terminals network on inland waterways should result in a concept of system reorganization, i.e. terminal planning methodology. By analysing relevant indicators according to the existing facts, and by using scientific methods and methodologies, the relevant criteria necessary to define the position and categories of intermodal terminals on inland waterways in the Republic of Croatia have been defined and evaluated on the examples of Sisak, Osijek, Vukovar and Slavonski Brod.KEY WORDS: intermodal terminal, intermodal transport, location criteria, inland waterways